Cell cycle markers and apoptotic proteins in oral tongue squamous cell carcinoma in young and elderly patients - BARNABÉ,Luan Éverton Galdino (2019)
Abstract The immunoexpression of p16, p53, and Bax in oral tongue squamous cell carcinoma (OTSCC) in young and elderly patients is assessed based on clinical and morphological parameters. The sample consists of 60 OTSCC cases: 30 in young (age ≤ 45 years) and 30 in elderly (age ≥ 60 years) patients. Clinical (tumor size, regional node metastasis, distant metastasis, and clinical stage) and morphological (histological grade of malignancy) parameters were evaluated. Immunohistochemical quantitative analysis was performed using anti-p16, anti-p53, and anti-Bax antibodies. None of the evaluated proteins exhibited statistically significant differences between young and elderly patients (p>0.05). There was a significant association of p16 immunoexpression with clinical parameters in elderly patients. There were no associations of p53 and Bax with any of the clinico-morphological parameters. Correlations between p16 and Bax and between p53 and Bax immunoexpression were observed in young patients (r = 0.363; p = 0.048) and in elderly patients (r = 0.433; p = 0.017), respectively. In conclusion, the assessed proteins could not be used to determine differences in the biological behavior of OTSCC between young and elderly patients. Therefore, all proteins activated the pro-apoptotic pathway of OTSCC in both groups.